Temperature Dependence of Lattice Parameters of Alpha-Zirconium - Versaci, R. A.; Ipohorski, M. (Comisión Nacional de Energía Atómica (CNEA), 1991)
Fil:Versaci, R. A. Comisión Nacional de Energía Atómica (CNEA). República Argentina